2006
DOI: 10.1101/gad.378706
|View full text |Cite
|
Sign up to set email alerts
|

Combined ectopic expression of Pdx1 and Ptf1a/p48 results in the stable conversion of posterior endoderm into endocrine and exocrine pancreatic tissue

Abstract: Patterning of the embryonic endoderm into distinct sets of precursor cells involves the precisely regulated activities of key transcription regulators. Ectopic, pan-endodermal activation of XPtf1a/p48 during pancreas precursor cell stages of Xenopus embryogenesis results in an expansion of the pancreatic territory, precisely within the borders of XlHbox8 expression. A combination of both activities is sufficient to expand the pancreatic precursor cell population also into more posterior portions of the endoder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
112
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(128 citation statements)
references
References 31 publications
13
112
1
2
Order By: Relevance
“…More evidence for an essential role for Ptf1a in committing cells with the MPC competence to produce all pancreatic lineages come from studies in Xenopus embryos. Afelik et al (2006) suggested that mis-expression of Ptf1a together with Pdx1 converts duodenum to pancreas, producing a ''giant pancreas'' that contained relatively normal acinar and endocrine proportions. One important role of Ptf1a after initial specification of the pancreas fate might be to ensure the rapid maintenance and/or upregulation of Pdx1 expression, possibly mediated by its transactivation via Area III of the Pdx1 promoter (Wiebe et al, 2007), with the idea being that Ptf1a/Pdx1 coexpression provides a more definitive pancreatic status to the MPC.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…More evidence for an essential role for Ptf1a in committing cells with the MPC competence to produce all pancreatic lineages come from studies in Xenopus embryos. Afelik et al (2006) suggested that mis-expression of Ptf1a together with Pdx1 converts duodenum to pancreas, producing a ''giant pancreas'' that contained relatively normal acinar and endocrine proportions. One important role of Ptf1a after initial specification of the pancreas fate might be to ensure the rapid maintenance and/or upregulation of Pdx1 expression, possibly mediated by its transactivation via Area III of the Pdx1 promoter (Wiebe et al, 2007), with the idea being that Ptf1a/Pdx1 coexpression provides a more definitive pancreatic status to the MPC.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…In its absence, foregut endoderm precursors assume an intestinal fate (14). Ptf1a also promotes ectopic pancreas fates from endoderm tissue (16)(17)(18). Mist1 is expressed in a wide array of secretory tissues and, in the adult pancreas, is only detected in acinar cells (19;20).…”
Section: Introductionmentioning
confidence: 99%
“…Within the endoderm, expression of XPtf1a/p48 is specifically restricted to the dorsal and ventral pancreatic buds (28,30). As for XlHbox8, the ventral expression domain of XPtf1a/p48 was found to be expanded in hhex-injected embryos, although to a lesser extent (Fig.…”
Section: Ectopic Expression Of Hhex Results In An Expansion Of the Enmentioning
confidence: 94%
“…XlHbox8 expression demarcates dorsal and ventral pancreatic buds, and part of stomach and duodenum at tail bud stages of development (27,28). The enlargement of the ventral foregut induced by ectopic hhex coincides with a specific expansion of ventral XlHbox8 expression domain (Fig.…”
Section: Ectopic Expression Of Hhex Results In An Expansion Of the Enmentioning
confidence: 99%